2018
DOI: 10.1186/s12864-018-4886-4
|View full text |Cite
|
Sign up to set email alerts
|

H4K20me3 co-localizes with activating histone modifications at transcriptionally dynamic regions in embryonic stem cells

Abstract: BackgroundBivalent chromatin domains consisting of the activating histone 3 lysine 4 trimethylation (H3K4me3) and repressive histone 3 lysine 27 trimethylation (H3K27me3) histone modifications are enriched at developmental genes that are repressed in embryonic stem cells but active during differentiation. However, it is unknown whether another repressive histone modification, histone 4 lysine 20 trimethylation (H4K20me3), co-localizes with activating histone marks in ES cells.ResultsHere, we describe the previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 48 publications
5
28
0
Order By: Relevance
“…These results suggest that H4K20me3 and H3K4me3 associate with common and distinct sets of transcripts. This finding is consistent with a previous report demonstrating that H4K20me3 and H3K4me3 co-localize at a subset of regions in ES cells (30). Heat maps also show enrichment of transcriptional and epigenetic regulator binding (RNAPII, RNAPII-Ser5P, RNAPII-Ser2P, and KDM5B), histone modification occupancy (H3K36me3, H3K4me3, and H3K4me2), and TF binding (MYC, E2f1, OCT4, ZFX, KLF4, SOX2, NANOG, ESRRB, and STAT3) at H4K20me3 (Fig.…”
Section: Relationship Between H4k20me3-and H3k4me3-associated Transcrsupporting
confidence: 94%
See 3 more Smart Citations
“…These results suggest that H4K20me3 and H3K4me3 associate with common and distinct sets of transcripts. This finding is consistent with a previous report demonstrating that H4K20me3 and H3K4me3 co-localize at a subset of regions in ES cells (30). Heat maps also show enrichment of transcriptional and epigenetic regulator binding (RNAPII, RNAPII-Ser5P, RNAPII-Ser2P, and KDM5B), histone modification occupancy (H3K36me3, H3K4me3, and H3K4me2), and TF binding (MYC, E2f1, OCT4, ZFX, KLF4, SOX2, NANOG, ESRRB, and STAT3) at H4K20me3 (Fig.…”
Section: Relationship Between H4k20me3-and H3k4me3-associated Transcrsupporting
confidence: 94%
“…Although H4K20me3-marked chromatin is thought to be a repressive histone modification, where it is enriched at pericentric hetereochromatin and is involved in repressing transcription of repetitive DNA elements (23,63,64), our data overall suggest that H4K20me3 interacts with many transcripts from loci that are actively transcribed in ES cells. Although H4K20me3 is mainly associated with heterochromatin regions, a recent study demonstrated that a subset of H4K20me3marked regions contain H3K4me3 (30). These previous findings demonstrating that H4K20me3 marks transcriptionally dynamic regions in ES cells is in alignment with results from this study, which show that expression of H4K20me3-associated RNAs is predominantly enriched in undifferentiated ES cells relative to differentiated cells (Fig.…”
Section: H4k20me3-and H3k4me3-associated Rnas In Es Cellssupporting
confidence: 90%
See 2 more Smart Citations
“…The presence of this mark at intronic transposons was inversely correlated with levels of gene expression but its effect on gene expression may be indirect, for example as a consequence of silencing intronic transposons. The distribution of H4K20me3 suggests a similar role to that observed in animals, where H4K20me3 is enriched at transposons and in heterochromatin [51][52][53] and where it has been shown to repress transposons [53]. Note that H4K20me3 appears to have a different role in land plants as it localises to euchromatin and is associated with transcriptional activation [54].…”
Section: Epigenetic Regulation In a Multicellular Brown Algamentioning
confidence: 77%